2005
DOI: 10.1051/0004-6361:20053085
|View full text |Cite
|
Sign up to set email alerts
|

NLTE ionization equilibrium of Nd II and Nd III in cool A and Ap stars

Abstract: Abstract.We investigate the formation of Nd - lines in the atmospheres of A-type stars with a comprehensive atomic model including 1651 levels of Nd , 607 levels of Nd  and the ground state of Nd . NLTE leads to overionization of Nd  which weakens the Nd  lines relative to the corresponding LTE line strengths at mild neodymium overabundance ([Nd/H] < 2.5) and amplifies them at higher [Nd/H] values. NLTE abundance corrections grow with the effective temperature and reach 0.6 dex at T eff = 9500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 19 publications
4
95
0
Order By: Relevance
“…The fact that Mashonkina et al (2005Mashonkina et al ( , 2009) find important non-LTE effects in formation of lines of Pr and Nd ii and iii in magnetic Ap stars with T eff as low as 7250 K suggests that non-LTE effects in Si could potentially be important well below the conventional limit of T eff ≈ 15 000 K.…”
Section: Non-lte Effects In B-type Starsmentioning
confidence: 99%
“…The fact that Mashonkina et al (2005Mashonkina et al ( , 2009) find important non-LTE effects in formation of lines of Pr and Nd ii and iii in magnetic Ap stars with T eff as low as 7250 K suggests that non-LTE effects in Si could potentially be important well below the conventional limit of T eff ≈ 15 000 K.…”
Section: Non-lte Effects In B-type Starsmentioning
confidence: 99%
“…Most of them come from the latest theoretical calculations performed by R. Kurucz 3 . Because of their large overabundance in atmospheres of Ap stars, rare-earth elements (REE) play an important and sometimes even dominating role in the appearance of spectroscopic features (Mashonkina et al , 2005 and can also affect the SED (Shulyak et al 2010b). Here we used the same line lists of REE elements as presented in Shulyak et al (2010b).…”
Section: Model Atmospheresmentioning
confidence: 99%
“…For Pr and Nd in γ Equ, we performed an NLTE stratification analysis as described in Mashonkina et al (2005Mashonkina et al ( , 2009) using a trial-and-error method and the observed equivalent widths of the lines of the first and second ions. In NLTE calculations magnetic field effects were roughly approximated by pseudomicroturbulent velocity individual for each line.…”
Section: Abundance and Stratification Analysismentioning
confidence: 99%
“…These data were supplemented by the transition probabilities for the observed and predicted lines of Pr ii−Pr iii ), Nd ii−Nd iii (Mashonkina et al 2005;Ryabchikova et al 2006), Eu iii (Wyart et al 2008), Tb iii and Dy iii (Ryabtsev, private communication), hereafter referred to as "ISAN data". For the latter two ions transition probability calculations were based on the extended term analysis.…”
Section: Ree Line Lists For Model Atmosphere Calculationmentioning
confidence: 99%